APAKAH INDIKATOR MAKROEKONOMI BERPENGARUH? BUKTI DARI KESEJAHTERAAN RUMAH TANGGA DAN DINAMIKA PERCERAIAN DI JAWA TENGAH PASCAPANDEMI - Sidhik Anggoro; Siti Fatimah Nurhayati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of economic factors on divorce in Central Java Province, with a focus on Gross Regional Domestic Product (GRDP) per capita, open unemployment rate, poverty rate, and per capita expenditure. This research employs a quantitative approach based on panel data covering 35 regencies/cities over the period 2019–2024. The analysis is conducted using panel data regression with the Fixed Effects Model (FEM), which is selected through the Chow Test and Hausman Test. The results indicate that per capita expenditure has a negative effect on the divorce rate, while GRDP per capita, the open unemployment rate, and the poverty rate do not show a significant effect. These findings suggest that the stability of household consumption and real economic well-being plays a more substantial role in influencing divorce dynamics compared to macroeconomic indicators. The implications of this study highlight that economic development policies should be directed toward increasing purchasing power, strengthening social protection, and enhancing family resilience. The novelty of this research lies in the use of a comprehensive approach that integrates macroeconomic and microeconomic indicators in the study of divorce during the post-COVID-19 economic recovery period.